Perspektif Mahasiswa Terhadap Transaksi Digital dalam Penggunaan Mobile Banking - Budiarti, Ayu Lestari; Wulandari, Eriska; Rodiah, Rita Deti; Anjani, Uli Silfia; Rozak, Rama Wijaya Abdul; Mulyani, Heni (Disclosure: Journal of Accounting and Finance, 2023)
Digital banking is a technology application developed to facilitate customer transactions. Currently, millennials are the target market for banking, especially in the use of digital banking, because they prefer something modern and instant. The trend of using mobile banking in the digital era is growing rapidly. Mobile banking is now one of the applications that are widely used by young people including students. This study aims to examine students’ perceptions of digital transactions using mobile banking. This research uses a qualitative descriptive method with data collection techniques that are carried out online through social media and are widespread in various regions in Indonesia using questionnaires, to active students in tertiary institutions, both public and private universities. The data analysis technique used is data reduction, namely by summarizing and sorting the data, presenting the data by describing the information text and paragraphs, and drawing conclusions. So, the research results show that most students who actively use mobile banking are influenced by various perceptions including perceptions of convenience and usability. But even so, there are still students who do not or do not use mobile banking, apart from that the use of mobile banking turns out there are still many deficiencies in it such as limited features and network disturbances.